Efficient isolation and proliferation of human adipose-derived mesenchymal stromal cells in xeno-free conditions - Fuoco, Natalia Langenfeld; de Oliveira, Rafael Guilen; Marcelino, Monica Yonashiro; Stessuk, Talita; Sakalem, Marna Eliana [UNESP]; Medina, Denis Aloisio Lopes; Modotti, Waldir Pereira; Forte, Andresa; Ribeiro-Paes, João Tadeu [UNESP] (Springer Nature, 2020)
Classical methods used for culture of adipose-derived mesenchymal stromal cells (ADSCs) use xenobiotic components, which may present a potential risk for biological contamination and/or elicit immunological reactions. Therefore, the aim of this study was to establish a xeno-free methodology for the isolation and proliferation of human ADSCs (hADSCs). hADSCs were isolated by enzymatic digestion or mechanical dissociation and cultured in the presence of fetal bovine serum or human platelet lysate. Proliferation curves were performed as a function of time from the cell culture and used to calculate the population doubling time. Immunophenotyping and differentiation tests were used to identify and characterize the hADSCs. Human ADSCs isolated and cultured in conventional or xenobiotic-free conditions peaked at different days but achieved similar maximum proliferation. The hADSCs differentiation ability was similar in all groups. The characterization of hADSCs by flow cytometry showed low contamination of the cultures by other cell types. The xenobiotic-free methodology described in this study is a feasible and reproducible alternative for isolation and proliferation of hADSCs. This methodology is in accordance with the recommendations of the National Health Surveillance Agency, which proposes avoidance of xenobiotic products.
Keywords: Adipose tissue; Fetal bovine serum (FBS); Mesenchymal stromal cells; Platelet lysate; Stem cells